ANALISIS PERILAKU SAFETY RIDING PADA WARGA KAMPUNG SAFETY DI KELURAHAN PANDEAN LAMPER KOTA SEMARANG - Yayan Adhanudin; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Safety riding is an effort to reduce the number of accidents as a result of traffic accidents with regard to the safety of riders and other road users.Kampung Safety is a CSR program (Cosporate Social Responsibility) from PT. Astra Motor International to support the movement of 'Indonesia, Ayo Aman Berlalu Lintas' and the first one was located in Pandean Lamper Sub-District Gayamsari District, Semarang City, Central Java.This study aimed to describe safety riding behavior in the residents of Kampung Safety in Pandean Lamper Urban Village Semarang. The type of this research is qualitative descriptive research with in-depth interview method and observation.The subject consist of four respondents, two safety agent, and three triangular subjects. The in-depth interview guide is based on Lawrence Green's behavioral theory of Predisposing, Enabling and Reinforcing.The results showed that the Predisposing Factors include knowledge about safety riding and kampung safety supported by giving a workshop by Astra Motor, positive support in the form of residents participation by removing all road hump in RW X area and marking side of the road with yellow and black colour , experience in committing an offense and having an accident and defeat in the safety riding race, and driving skills supported by training on safety riding agent using Honda Simulator Riding Trainer. Enabling factors include regulations about riding in village area, information media include wall magazines, safety riding post and sanctions in the form of reprimands. Reinforcing factors are the support of family members to remind each other to be carefull during riding, agent safety riding which has been designated by residents who are considered to have better driving skillsand good communication between residents